ENGAGING NEARBY POPULATION FOR DEVELOPING HALMAHERA WALKING SHARK HABITAT AS MARINE TOURISM POTENTIAL IN NORTH MOLUCCAS - Dwi Puspitasari; Surya Albani; Maria Holy Octavia Sitorus; Aishah Gray; Darmawan Ahmad Mukharror (Politeknik Pariwisata Makassar, 2025)
The Halmahera walking shark (Hemiscyllium halmahera) represents a unique marine species endemic to North Moluccas, Indonesia, with significant potential to become a focal point of sustainable marine tourism. This study explores the role of engaging nearby coastal populations in supporting the development of walking shark habitats as tourism assets. Data were obtained through community surveys and stakeholder interviews. Findings reveal that local communities demonstrate strong interest in marine tourism initiatives but require capacity-building in ecotourism practices, conservation awareness, and benefit-sharing mechanisms. Effective community engagement enhances stewardship of walking shark habitats, reduces the risk of unsustainable exploitation, and increases socio-economic resilience through alternative livelihoods such as guiding, homestays, and small-scale enterprises. The integration of community perspectives into tourism planning also fosters local ownership and long-term conservation commitment. The results emphasize that the success of marine tourism centered on the Halmahera walking shark depends not only on ecological suitability but also on the active participation and empowerment of nearby populations through inclusive management frameworks.